(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: (1) To investigate language characteristics in children with CP treated and monitored at Nghe An Obstetrics and Pediatrics Hospital in 2024. (2) To investigate speech characteristics in children with CP treated and monitored at Nghe An Obstetrics and Pediatrics Hospital in 2024. Subjects and methods: This cross-sectional descriptive study included 34 children with cerebral palsy treated and monitored at Nghe An Obstetrics and Pediatrics Hospital from March to September 2024. Results: The average age of participants was 43,13 ± 20,93 months, with 61,76% being male. Regarding language, 88,24% experienced difficulties in receptive and expressive language, 41,18% could not understand instructions, and 47,06% could not produce single words. Regarding speech, 100% of the children exhibited limited phonemic repertoire and reduced speech intelligibility, with 44,12% having incomprehensible speech. 88,24% belonged to the combined difficulty group, while 11,76% had speech clarity issues. Children with more severe CP levels faced greater challenges in both language and speech (p<0,05). Conclusions: The study highlights significant language and speech difficulties in children with CP.